2022
DOI: 10.1002/imt2.20
|View full text |Cite
|
Sign up to set email alerts
|

A neural network‐based framework to understand the type 2 diabetes‐related alteration of the human gut microbiome

Abstract: The identification of microbial markers adequate to delineate the disease‐related microbiome alterations from the complex human gut microbiota is of great interest. Here, we develop a framework combining neural network (NN) and random forest, resulting in 40 marker species and 90 marker genes identified from the metagenomic data set (185 healthy and 183 type 2 diabetes [T2D] samples), respectively. In terms of these markers, the NN model obtained higher accuracy in classifying the T2D‐related samples than othe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…However, methods like Principal Component Analysis have shown satisfying results when applied on this data, leading to a slight improvement in prediction. The other way around, ML methods like [48] and [146] aim to extract top decisive features or markers for disease prediction to understand key roles played by these features in the apparition of a disease.…”
Section: Resultsmentioning
confidence: 99%
“…However, methods like Principal Component Analysis have shown satisfying results when applied on this data, leading to a slight improvement in prediction. The other way around, ML methods like [48] and [146] aim to extract top decisive features or markers for disease prediction to understand key roles played by these features in the apparition of a disease.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have attempted to incorporate multilayer perceptions (MLP) or recurrent neural networks (RNN) into omics data analysis, primarily on RNA sequencing data. For instance, Guo et al proposed a combined framework with an MLP and RF to understand the human microbiome for identifying the T2D-related microbial markers. It trained an MLP model with biomarkers selected by RF and achieved better performance than other machine learning methods.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Guo et al 26 proposed a combined framework with an MLP and RF to understand the human microbiome for identifying the T2D-related microbial markers. It trained an MLP model with biomarkers selected by RF and achieved better performance than other machine learning methods.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, using more than one method for analysis may be more susceptible to noisy samples. Some researchers have found that by combining RF with other algorithms, RF can use the mechanism of multiple tree voting to cancel out some noise [ 20 ]. However, studies have yet to report combining RF and WGCNA to better analyse and mine the intestinal microflora.…”
Section: Introductionmentioning
confidence: 99%